BUSINESS INTELLIGENCE-HISTORICAL DEVELOPMENT AND PERSPECTIVES (Yearbook - Faculty of Economics, 2018)
Business intelligence is the logical progress in future managerial thinking for IT. While a growing number of companies have implemented the data storage (data warehousing), very little use in the implementation of business intelligence. In many companies, this data storage is largely limited to the preparation of several reports with vague understanding of how for this information will benefit the organization. However, some European comapnies, and companies of our environment go a step ahead and exploit the true potential of business intelligence. Business intelligence combines products, technology and methods of organizing key information needed by management to improve performance and increase profits. More broadly, we should think of business intelligence as a set of business information and business analysis in the context of key business processes that lead to decisions and actions and resulting in improved business performance.